Construction of developmental lineage relationships in the mouse mammary gland by single-cell RNA profiling - Bhupinder Pal (Nature Portfolio, 2017)
The mammary epithelium comprises two cell lineages but the heterogeneity amongst these during development is unclear. Here, the authors report single-cell RNA sequencing of the mouse mammary epithelium at four developmental stages, revealing diversity in both compartments and a transcriptional shift with puberty onset.